State of food insecurity in the CARICOM Caribbean : executive summary - meeting the 2015 hunger targets, taking stock of uneven progress (FAO. Office for the Caribbean BridgetownBB, 2015)
Presents a summary of the current situation on undernourishment, food and nutrition security, and policies, programmes and actions in place to advance food and nutrition security in the CARICOM countries.
Keywords: FOOD SECURITY